PENYULUHAN EDUKASI SECARA DARING TENTANG MEMAHAMI DAN MENCEGAH KANKER SERVIKS - Ageng Septa Rini; Magdalena Tri Putri Apriyani (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Cervical cancer is a disease that is categorized as a malignant disease of the cervix or uterine cervix. Approximately 90% or 270,000 deaths resulting from cervical cancer in 2017 occur in countries with low and middle income. The purpose of this study was to determine mother's knowledge about cervical cancer prevention. Method In this community service the researcher provides information education to women of childbearing age regarding Understanding and Preventing Cervical Cancer, the researcher distributes flyers to respondents to take part in this counseling in online community service (Zoommeeting) in Bojonggede Village, Bogor. Participants will fill out a questionnaire in the form of a Googleform. The results of the recapitulation of the pretest and posttest, that is, from the 74 participants who answered the pretest results, an average of 60% of the answers were correct and 40% of the answers were wrong. the answer is wrong. It can be concluded that after counseling the posttest results are better so that the mother understands and understands preventing Cervical Cancer. It is recommended that women of childbearing age maintain personal hygiene and prevent cervical cancer with early examinations such as an IVA test and acetic acid.